Infection risks by aerosol transmission during sporting activities - Asbach, C.; Scheuch, G. (Deutsche Zeitschrift für Sportmedizin, 2021)
The current pandemic has bestowed many restrictions on both professional and amateur sporting activities and led to the postponement of major sporting events like the European Soccer Championship and the Olympic Games from 2020 to 2021.